Goldberg–Shprintzen syndrome is determined by the absence, or reduced expression levels, of KIFBP. Issue 11 (16th September 2020) - MacKenzie, Katherine C.; de Graaf, Bianca M.; Syrimis, Andreas; Zhao, Yuying; Brosens, Erwin; Mancini, Grazia M. S.; Schot, Rachel; Halley, Dicky; Wilke, Martina; Vøllo, Arve; Flinter, Frances; Green, Andrew; et al.
Abstract: Goldberg–Shprintzen syndrome (GOSHS) is caused by loss of function variants in the kinesin binding protein gene ( KIFBP ). However, the phenotypic range of this syndrome is wide, indicating that other factors may play a role. To date, 37 patients with GOSHS have been reported. Here, we document nine new patients with variants in KIFBP : seven with nonsense variants and two with missense variants. To our knowledge, this is the first time that missense variants have been reported in GOSHS. We functionally investigated the effect of the variants identified, in an attempt to find a genotype–phenotype correlation. We also determined whether common Hirschsprung disease (HSCR)‐associated single nucleotide polymorphisms (SNPs), could explain the presence of HSCR in GOSHS. Our results showed that the missense variants led to reduced expression of KIFBP, while the truncating variants resulted in lack of protein. However, no correlation was found between the severity of GOSHS and the location of the variants. We were also unable to find a correlation between common HSCR‐associated SNPs, and HSCR development in GOSHS. In conclusion, we show that reduced, as well as lack of KIFBP expression can lead to GOSHS, and our results suggest that a threshold expression of KIFBP may modulate phenotypic variability of the disease.